1978
DOI: 10.1159/000102409
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Spinal Cord Stimulation for Spastic Movement Disorders

Abstract: Spinal cord stimulation seems today a promising method to improve spasticity. The experiences of two different clinics (Zürich and Freiburg i.Br.) are reported with long-term assessment up to 28 months. The objective data with measurement of stretch and H reflexes support the clinical results. An experimental study on animals does not permit a definitive explanation, but some hypotheses can be suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

1979
1979
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 4 publications
2
31
0
Order By: Relevance
“…25 Another potential source of the effects observed here can be drawn from the reports that stimulation of the long tracts of the spinal cord reduces responsiveness to muscle spindle afferent input after spinal cord lesioning in cat models and SCI in humans. 23,24,43,44 Here, we applied tSCS with adequate intensity to produce paraesthesias that are generally associated with posteriorcolumn depolarization during epidural SCS. [45][46][47] Modeling of tSCS-induced currents, however, has shown that posterior column fibers have considerably higher thresholds than the posterior root fibers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Another potential source of the effects observed here can be drawn from the reports that stimulation of the long tracts of the spinal cord reduces responsiveness to muscle spindle afferent input after spinal cord lesioning in cat models and SCI in humans. 23,24,43,44 Here, we applied tSCS with adequate intensity to produce paraesthesias that are generally associated with posteriorcolumn depolarization during epidural SCS. [45][46][47] Modeling of tSCS-induced currents, however, has shown that posterior column fibers have considerably higher thresholds than the posterior root fibers.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with motor-complete and incomplete SCI, epidural SCS was applied below and above the lesion at vertebral levels ranging from C2 to T10 and at stimulation frequencies of 30-1500 Hz, with variable results. [18][19][20][21][22] Dimitrijevic et al 23,24 suggested that the diversity of physiological conditions after SCI and the placement of the epidural electrodes determined the efficacy of SCS in spasticity control. While interest in this technique declined in the 1990s, Pinter et al 25 revisited its use in individuals with chronic SCI.…”
Section: Introductionmentioning
confidence: 99%
“…7 Siegfried et al, who treated 15 chronic SCI patients by placing the electrode above the lesion, failed to con®rm this ®nding. 8 In an eort to clarify the precise impact of the site of stimulation, Dimitrijevic et al used SCS in a sample of 58 SCI patients and found spasticity to be more eectively controlled when the electrode was placed below, rather than above, the lesion. 9 This ®nding was again con®rmed by Barolat et al who, based on a total of 48 patients, concluded that SCS applied below the level of the lesion was an eective and safe approach to controlling SCI-related spasms.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in spinal cord stim ulation (SCS) for modification of im paired m otor activity have presented an opportunity for the clini cal researcher to observe [1, 4-7, 9, 12, 13, 15, 21-23], to record [13,17,21], and to study changes in abnorm al m otor activity in patients with upper m otor neuron dysfunctions [8]. However, from an experimental design point of view, the situation is rather complicated, due to the fact that the currently used stim ulation param eters require continuous ap plication o f the stimulus.…”
Section: Introductionmentioning
confidence: 99%